2022
DOI: 10.3389/fpubh.2022.965306
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive breastfeeding and women's psychological well-being during the first wave of COVID-19 pandemic in Italy

Abstract: BackgroundAt the onset of the COVID-19 pandemic, support for breastfeeding was disrupted in many countries. Italy was severely impacted by the pandemic and is known to have the lowest exclusive breastfeeding rate of all European countries. Considering the inverse association between anxiety and breastfeeding, maternal concerns about the COVID-19 emergency could reduce breastfeeding rates. The aim of the study is to explore the association between infant feeding practices and maternal COVID-19 concerns.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
3
0
2
Order By: Relevance
“…According to Lee et al [ 36 ], it was found that mother’s mental health had more influence on young children’s health prevention behavior than other groups. During the coronavirus pandemic, there have been many studies examining negative mental health factors such as anxiety [ 37 ], psychological instability [ 38 ], harsh parenting [ 39 ], and lack of emotional care [ 40 ] among mothers with young children during the COVID-19 pandemic. Maternal confidence is an important factor that positively influences preventive health behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…According to Lee et al [ 36 ], it was found that mother’s mental health had more influence on young children’s health prevention behavior than other groups. During the coronavirus pandemic, there have been many studies examining negative mental health factors such as anxiety [ 37 ], psychological instability [ 38 ], harsh parenting [ 39 ], and lack of emotional care [ 40 ] among mothers with young children during the COVID-19 pandemic. Maternal confidence is an important factor that positively influences preventive health behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…1. Beban Emosional Berdasarkan hasil penelitian ditemukan penelitian di Negara Turkey, Inggris, Swiss, Spanyol, Italy, Amerika Serikat yang dilakukan oleh (Aşcı et al, 2022;Costantini et al, 2021;Jacob et al, 2022;Lambelet et al, 2021;Pereira et al, 2020;Ravaldi et al, 2022) menyebutkan bahwa beban emosional yang dirasakan oleh ibu menyusui seperti perasaan sedih, rasa bersalah, cemas dan ketakutan.…”
Section: Pembahasanunclassified
“…Hal tersebut terlihat dari pernyataan yang ditemukan oleh (Lambelet et al, 2021;Pereira et al, 2020;Ravaldi et al, 2022) menyebutkan bahwa pengalaman ibu menyusui selama pandemic covid-19 yaitu ibu merasa cemas dan takut Ketika mereka di diagnosis covid-19. Bahkan dari beberapa penelitian ada yang menyebutkan bahwa ibu mengalami stress dan depresi saat di diagnosis covid-19 tersebut.…”
Section: Pembahasanunclassified
“…Our previous research, conducted during the initial phase of the COVID-19 lockdown in Italy, provided preliminary insights into the emotional experiences of pregnant and postpartum women [15][16][17]. These studies found that pregnant women experienced significant psychological distress during the pandemic, including symptoms of depression, anxiety, and stress.…”
Section: Introductionmentioning
confidence: 99%
“…These studies found that pregnant women experienced significant psychological distress during the pandemic, including symptoms of depression, anxiety, and stress. Furthermore, exclusive breastfeeding was found to serve as an independent protective factor for women's mental health during the pandemic [17].…”
Section: Introductionmentioning
confidence: 99%